A new species of Cerapus (Amphipoda, Senticaudata, Ischyroceridae) from Mae Klong Estuary, with a discussion on their nesting and types of mating behaviour - Chanikan Katnoum; Tosaphol Saetung Keetapithchayakul; Azman Abdul Rahim; Koraon Wongkamhaeng (Zoosystematics and Evolution, 2023)
The first representative of the genus Cerapus in the Gulf of Thailand, Cerapus rivulus sp. nov., is described from specimens sampled from Mae Klong Estuary, the inner Gulf of Thailand. The main identifying characteristics of this new amphipod species are pereonites 1 and 2 without constriction; male gnathopod propodus palm transverse with long posterior defining tooth and well-developed anterodistal recurved tooth adjacent to propodus articulation; pereopod 6 coxa without fine fringe setae ventrally, basis with setae on posterior margin; and telson with deep cleft. An updated identification key for the 25 known species in the genus is also presented. A discussion on their nesting and types of mating behaviour is provided.